Analysis and Simulation for Three-phase Voltage-source PWM Rectifier Circuit Based on LCL Filter - GAO Yang; HU Jiaxi; GUO Shiming; CHEN Tao; LIU Linman (Kongzhi Yu Xinxi Jishu)
The problems such as nonlinear and harmonic current etc. are existing in power electronic devices(e.g., diode and thyristor rectifiers ). A solution to avoid mentioned problems is adopted by using the three-phase PWM rectifier which has the characteristics of input current closing to sinusoidal, controllable reactive power and bi-directional power flow capability. We should add filter to the circuit in order to eliminate distortion and harmonious. Because inductance value of traditional L filter with pure inductance is usually large, the problems such as large volume, high cost and slow dynamic response will arise. Traditional L filter is replaced by the LCL filter, on an account of inductor value of LCL filter smaller than the L filter’s, which can solve the problems brought by the traditional filter. Through the Matlab modeling and simulation, the correctness of theory analysis is verified.